Effect of daily salinity fluctuation on the intraspecific interactions of a euhalophyte (Suaeda salsa) along a salinity gradient. (11th January 2022) - Ma, Hua; Cui, Li-Juan; Li, Wei; Ning, Yu; Lei, Yin-Ru; Pan, Xu; Wang, Yi-Fei; Zhang, Man-Yin
Abstract: Heterogeneity of soil salinity is a prominent environmental characteristic in the intertidal zone of estuaries, affecting the plant growth and the shift of biotic interactions in the salt marsh. This study aims to examine the interactive effects of a salinity gradient and salinity fluctuations on intraspecific interactions of a euhalophyte. We assessed the impact of daily fluctuating salinity on the outcome of intraspecific interactions by cultivating seeds of Suaeda salsa (Chenopodiaceae) in river sand. The experiment was conducted in a greenhouse with three treatments: daily salinity fluctuations (static and fluctuating salinity), a salinity gradient (200 and 400 mmol L −1 ) and three planting densities (1, 2 and 4 plants/pot). First, height and biomass of plants were measured at both the start and end of the experiment. Then, the growth indexes and log response ratio of S. salsa were analyzed. The outcome of intraspecific interactions of S. salsa shifted from competition in low salinity to facilitation in high salinity, and high conspecific density strengthened the competition and facilitation intensities. Daily salinity fluctuation did not significantly affect the plant growth and the outcome of intraspecific interactions, but did have a significant influence on belowground biomass. Our results suggest that the stress-gradient hypothesis may apply to predicting the variation of the intraspecific relationship of a salt-tolerant species along a salinity gradient, and the magnitude of this variation is density dependent. These findings help us understand how individuals and populations of a euhalophyte species respond to the natural variation or human modification of salinity conditions.